Comparison of Tumor Non-specific and PD-L1 Specific Imaging by Near-Infrared Fluorescence/Cerenkov Luminescence Dual-Modality In-situ Imaging - Linhan Zhang MD; Lianmeng Zhao MS; Xue Lin MD; Sheng Zhao MD; Wenbin Pan MS; Dandan Wang MD; Zhongqi Sun MD; Jinping Li MD; Zonghui Liang MD; Rongjun Zhang MS; Huijie Jiang MD (Molecular Imaging)
Background Labeled antibodies are excellent imaging agents in oncology to non-invasively visualize cancer-related antigens expression levels. However, tumor tracer uptake (TTU) of specific antibodies in-vivo may be inferior to non-specific IgG in some cases. Objectives To explore factors affecting labeled antibody visualization by PD-L1 specific and non-specific imaging of nude mouse tumors. Methods TTU was observed in RKO model on Cerenkov luminescence (CL) and near-infrared fluorescence (NIRF) imaging of radionuclide 131 I or NIRF dyes labeled Atezolizumab and IgG. A mixture of NIRF dyes labeled Atezolizumab and 131 I-labeled IgG was injected, and TTU was observed in the RKO and HCT8 model by NIRF/CL dual-modality in-situ imaging. TTU were observed by 131 I-labeled Atezolizumab and IgG in-vitro distribution. Results Labeled IgG concentrated more in tumors than Atezolizumab. NIRF/CL imaging in 24 to 168 h showed that TTU gradually decreased over time, which decreased more slowly on CL imaging compared to NIRF imaging. The distribution data in-vitro showed that TTU of 131 I-labeled IgG was higher than that of 131 I-labeled Atezolizumab at any time point. Conclusion Non-specific IgG may not be suitable as a control for Atezolizumab in comparing tumor PD-L1 expression in nude mice via labeled antibody optical imaging under certain circumstances.